The Relationship between Theoretical Orientation and Countertransference Expectations: Implications for Ethical Dilemmas and Risk Management. (27th March 2015) - Gordon, Robert M.; Gazzillo, Francesco; Blake, Andrea; Bornstein, Robert F.; Etzi, Janet; Lingiardi, Vittorio; McWilliams, Nancy; Rothery, Cheryll; Tasso, Anthony F.
Abstract : Countertransference (CT) awareness is widely considered valuable for differential diagnosis and the proactive management of ethical dilemmas. We predicted that the more practitioners' theoretical orientation (TO) emphasizes insight into the dynamics of subjective mental life, the better they will be at using their CT expectations in differential diagnosis with high‐risk patients. To test this hypothesis, we compared psychodynamic therapy (PDT) practitioners who emphasize insight into subjective mental life with practitioners who do not emphasize this epistemology. Results indicated that PDT practitioners expected significantly more CT than practitioners of cognitive–behavioural therapy (CBT) and other practitioners (e.g., family systems, humanistic/existential and eclectic) to patients with borderline personality organization overall. PDT practitioners had significantly more CT expectations to patients with borderline‐level pathologies as compared with neurotic‐level patients than both CBT and other practitioners. PDT practitioners were significantly more expectant of CT issues than CBT practitioners with respect to the personality disorders most associated with acting out and risk management problems (e.g., paranoid, psychopathic, narcissistic, sadistic, sadomasochistic, masochistic, hypomanic, passive–aggressive, counterdependent and counterphobic). The other practitioners generally had CT expectations between PDT and CBT. These findings suggest that clinical training into CT may be useful in differential diagnoses and in helping to avoid ethical dilemmas regardless of one's theoretical preference. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: Insight into countertransference can be used to help with differential diagnoses and to help prevent possible management problems with acting out patients. The Psychodynamic Diagnostic Manual is a useful taxonomy in that it includes countertransference as a diagnostic aid.